PERKEMBANGAN PEMIKIRAN FILSAFAT ISLAM MODERN (SEBUAH TINJAUAN UMUM) - Wardani, Wardani (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2015)
This article is aimed to deal with the development of Islamic philosophy in modern era in many countries, both in theEast and the West, in the world commonly, and in Indonesia particularly. Islamic philosophy in this era has grownthrough four stages. Firstly, at the beginning of 19th century, when the modernization in Muslim countries has beeninitiated by Jaml al-Dn al-Afghn. Secondly, since 19th until 20th century, when some orientalists among Jews havestudied the Islamic philosophy. Thirdly, post-World War II, when the Islamic philosophy has become the concern ofthe Eastern and Western scholars. Fourthly, the golden age of Islamic philosophy has come, since 20th centuryhitherto, when the bordes has fused in the sense that both Western and Eastern scholars have collaborated in jointintellectualagenda to study of Islamic philosophy. The Study of Islamic philosophy in Indonesia, in particular, haspassed three stages of development; firstly, in 1960-1970s, the stage of consolidation has begun through efforts carriedout by Harun Nasution to cultivate rational thought in the mind of Indonesian Moslems; secondly, in 1980-1990s,the stage of institutionalization has begun when the department of theology and philosophy at the Faculty of Ushl al-Dn at Syarif Hidayatullah State Institute for Islamic Studies in Jakarta has been initiated in 1982; finally, since1990 hitherto, the stage of functionalization, when the Islamic philosophy has been studied in Islamic universities, andeven functionalized to solve many problems.